«І сміх, і гріх»: курйозні випадки з життя духовенства Чернігівської єпархії у ХІХ ст. - Тарасенко, О. (Сiверянський лiтопис, 2016)
У статті розглядаються питання субкультури, типи поведінки, колективна
психологія духовенства як суспільної верстви населення у ХІХ ст. Яскравим проявом
цих аспектів дослідження є різні курйозні випадки з повсякденного життя та професійної діяльності священнослужителів. У статті наведені характерні приклади
подібної поведінки, запроваджено до наукового обігу новий документальний матеріал з історії Чернігівської єпархії. В статье анализируются вопросы субкультуры, типы поведения, коллективная
психология духовенства как общественного сословия в ХІХ в. Ярким проявлением
этих аспектов исследования являются различные курьезные случаи из повседневной
жизни и профессиональной деятельности священнослужителей. В статье приведены характерные примеры подобного поведения, вводится в научный оборот новый документальный материал из истории Черниговской епархии. In the article are analyzed the questions of subculture, types of conduct, collective psychology
of clergy as a public estate in of XIX centuries. Everyday life of clergy, her mentality,
need further studios, exposure and input turnover of new information generators, analysis
and comprehension of her, that is an actual scientific task. The bright displays of these aspects
of research are different odd cases from everyday life and professional activity of priests.
During of ХІХ century took place gradual corporate reserve of the clergy state.
This process passed contrary to general wave of increase social mobility in the conditions
of speed-up capitalist development. As a mission of clergy consisted in spiritual and moral
leadership, maintenance of authority of the church setting, then a removal is from folk public,
cultivation of corporate connections small and negative consequences.
All social close system produce subculture, the standards of behavior and collective
psychology, inherent to her. Without regard to the specific of church service, laughter and
eccentric conduct peculiar to the clergy. Although in time the increase of aggressiveness is felt
in jokes, that it is possible to explain a certain social stalemate. Often the funny balanced
on the faucet of the violation of human and christian norms of the moral and standards of
behavior accepted in general lines. To our opinion, it is a certificate of the deep crisis of the
spiritual state, caused both church by politics the states and previous behavior of clergy that
aimed to preserve the class privileges. In the conditions of rapid socio-economic and social
and political development on the fracture of ХІХ – ХХ century it ended up in the situation
of certain social deadlock.
In the article are resulted the characteristic examples of similar conduct, new documentary
material is entered in a scientific turn from history of the Chernigov diocese.